Operating systems : internals and design principles - Stallings, William (Boston, Massachusetts : Pearson, 2012)
This book is about the concepts, structure, and mechanisms of operating systems. Its purpose is to present, as clearly and completely as possible, the nature and characteristics of modern-day operating systems.
Part 1. Background -- Chapter 1. Computer system overview -- Chapter 2. Operating system overview -- Part 2. Processes -- Chapter 3. Process description and control -- Chapter 4. Threads -- Chapter 5. Concurrency : Mutual exclusion and synchronization -- Chapter 6 : Concurrency : deadlock and starvation -- Part 3. Memory -- Chapter 7. Memory management -- Chapter 8. Virtual memory -- Part 4 : Scheduling -- Chapter 9. Uniprocessor scheduling -- Chapter 10. Multiprocessor and real-time scheduling -- Part 5 : Input/output and files -- Chapter 11. I/O management and disk scheduling -- Chapter 12. File management -- Part 6. Embedded systems -- Chapter 13. Embedded operating systems -- Part 7. Computer security -- Chapter 14. Computer security threats -- Chapter 15. Computer security threats -- Part 8. Distributed systems -- Chapter 16. Distributed processing, client/server, and cluster
Includes bibliographical references and index.
Keywords: OPERATING SYSTEMS (COMPUTERS)